The Relationship between Islamic Boarding Schools and Islamic Politics: Democratic Literacy Education for First-Time Voters in West Java - Kunkunrat Kunkunrat; Ade Priangani; Willya Achmad (Nazhruna: Jurnal Pendidikan Islam, 2026)
Islamic boarding schools (pesantren) are important institutions for shaping students' (santri) political knowledge, especially among first-time voters. Democratic literacy is a key component in developing rational, critical, and responsible voters. Nevertheless, this relationship is still viewed in the narrow context of pesantren as a political weapon to mobilize an Islamic group, leading to a need for a deeper exploration of pesantren's educational role in democracy. Thus, this study seeks to examine the interplay between pesantren and Islamic politics in the context of democratic literacy education for first-time voters in West Java. This study is qualitative in nature and employs a case study method. These findings indicate that pesantren influences students' (santri) democratic literacy by instilling Islamic moral values, rational and critical political literacy, and maslahatan, or an understanding of the public interest. The influence of the kiai (Islamic clerics) is normative and ethical, but does not necessarily determine students' political preferences. As first-time voters, students show moderate and inclusive integration of Islamic values with democratic principles. This study shows that pesantrens are active contributors to generating first-time voters through democratic awareness, political responsibility, and a quality-of-democracy orientation.